457. Relationship Between Healthcare Worker (HCW) Perception of Safety and Rates of Healthcare-Associated Infections (HAI) and Hand Hygiene (HH) Compliance. (26th November 2018) - Kowalkowski, Marc; Schmidt, Monica; Kester, Shelley; Fischer, Kristin; Passaretti, Catherine
Abstract: Background: Many facilities complete the Agency for Healthcare Research and Quality (AHRQ) patient safety culture survey. Our goal was to evaluate associations between healthcare worker (HCW) responses to AHRQ patient safety culture survey questions and unit performance on healthcare-associated infections (HAI) and hand hygiene compliance. Methods: 11, 257 HCW across 10 acute care hospitals and four rehabilitation facilities completed the 2016 AHRQ patient safety survey. Unit-level standardized infection ratios (SIRs) were calculated for central line-associated bloodstream infections (CLABSIs) and catheter-associated urinary tract infections (CAUTIs) and standardized utilization ratios (SURs) for Foley catheter use. SIRs and SURs <1 met HAI performance goals. Hand-hygiene compliance was captured via secret-shopper methods and ≥75% used as the cut-off for meeting compliance goals. Unit-aggregated survey responses were compared between units that did vs. did not meet SIR, SUR goals for the year, and HH goals for the quarter, prior to survey distribution, using two-sample t-tests. Results: Fewer HCW on low-HH compliance units (i.e., <75%; n = 179 units) responded positively to questions pertaining to overall perception of safety, frequency of events reported, supervisor/manager expectations/actions promoting safety, organization learning, teamwork within units, communication openness, and nonpunitive response to errors, than HCW on high-compliance units (i.e., >75%; n = 69 units; P < 0.05). More HCW on units with CAUTI SIR <1 ( n = 40 units) responded positively to supervisor/manager expectations/actions promoting safety, teamwork across units, and hospital handoffs, compared with HCW on units with SIR ≥1 ( n = 20; P < 0.05). Fewer HCW on units with Foley SUR <1 ( n = 27 units) responded positively to questions on supervisor/manager expectations/actions promoting safety and teamwork within units, than HCW on units with SUR ≥1 ( n = 22; P < 0.05). We observed no associations between CLABSI SIR performance and AHRQ safety survey responses. Conclusion: HCW perceptions of unit safety culture can be associated with HAI and HH compliance performance. Unit performance/compliance was most commonly associated with supervisor expectations suggesting a key managerial component to promoting safety culture. Disclosures: All authors: No reported disclosures.